On equivalent representations and properties of faces of the cone of copositive matrices. (2nd November 2022) - Kostyukova, O. I.; Tchemisova, T. V.
Abstract : The paper is devoted to the study of the cone C O P p of copositive matrices. Based on the concept of immobile indices known from semi-infinite optimization, we define zero and minimal zero vectors of a subset of the cone C O P p and use them to obtain different representations of the faces of C O P p and the corresponding dual cones. The minimal face of C O P p containing a given convex subset of this cone is described, and some propositions are proved that allow obtaining equivalent descriptions of the feasible sets of copositive problems.